Decline in the lung cancer hazard: a prospective study of the mortality of iron ore miners in Cumbria. - Kinlen, L J (1988)
The mortality of 1947 Cumbrian iron ore miners has been studied over the period 1939-82 in relation to that among other groups of men in England and Wales: (a) all men, (b) men of similar social class, and (c) men living in similar types of (mainly rural) area. Significant excesses were found for deaths from tuberculosis and respiratory diseases compared with each of the reference populations. Lung cancer showed an excess over that in comparable (mainly rural) areas of England and Wales, as reported in a previous study using a proportionate method of analysis and which covered the period 1948-67 but no appreciable excess after 1967. Reasons for this decline are discussed.